Studies on Erosional Behaviour of the Soils of Jayakwadi Catchment - Rudra, P.; Gjatol, S.G/ (Journal of Soil and Water Conservation, 2022)
Studies on erosional behaviour of the soils of the soils of Jayakwadi catchment were made. The variations in geology, topography, vegetation, climate and the soil characteristics are responsible for differential soil erosion. Eight erosion intensity mapping units were studied during field survey and their relative erosivity/weightage values were correlated for differential soil erosion. The erosion ratio obtained from the physico-chetnical analysis of the soils more or less tallied with the weightage values assessed during field surveys. The erosion ratios were found positively correlated with the dispersion ratios, suspension percentages and percolation ratios. A significant negative correlation of erosion ratios was observed with clay’ ME, CEC and clay.